The voluntary intake in growing pigs of four ensiled forage species - Sarria, P.I.; Martens, Siriwan D. (2013)
Forage can potentially be food resource for pig feeding in the tropics. The palatability of silages by pigs may be better than that of fresh forage. Foliage silage contains more dry matter than green forage and has a pleasant smell. Thirty commercial pigs (47.0 ± 4.7 kg live weight LW), were used to assess the silage intake capacity of pigs when feeding the legumes Clitoria ternatea, Centrosema brasilianum, Cratylia argentea and the Brachiaria grass hybrid Mulato II. The silages were offered ad libitum as a supplement to a normal balanced diet based on maize and soy bean meal. A crossover design was applied comprising five treatments, Control and the four silage supplements respectively. Daily consumption of dry matter -expressed in g of DMkg-1 metabolic LW- were similar (p>0.05) for diets containing C. argentea, C. ternatea and the Control. Daily consumption of C. brasilianum and Brachiaria was significantly lower (p<0.001). In conclusion, C. argentea and C. ternatea silages have the potential to serve as feed supplement in pig diets.